PENGARUH KEPADATAN PENDUDUK, TINGKAT KEMANDIRIAN DAERAH DAN TAX EFFORT TERHADAP BELANJA MODAL PEMERINTAH KABUPATEN/KOTA PROVINSI JAWA TIMUR - YUNITA, ARIS (Jurnal Akuntansi AKUNESA, 2017)
This study aims to analyze the factors that affect the allocation of capital expenditure district/city government East Java. The independent variables used are population density, the level of regional independence and tax effort and the dependent variable is capital expenditure. The type of this research is quantitative research using secondary data. Research data were analyzed by using multiple linear regression. The sample used is 38 district/city of East Java province in 2011-2015. The results showed that the density of the population had a negative effect on capital expenditure, while the level of regional independence and tax effort had a positive effect on capital expenditure.    Keywords: population density, regional independence, tax effort, capital                 expenditure